MONITORING AMBIENT TEX CONCENTRATIONS EXPOSURE OF RECREATIONAL RUNNERS IN BANDUNG - Kevin Ardyanta Harsana, Gde
TEX refers to hydrocarbons such as toluene, ethylbenzene, and xylene. Cigarette smoke and automobile and aviation emissions are the main human-caused sources of TEX chemicals. Hence, TEX can be deposited in various spaces, especially in ambient air that recreational runners breathe daily. Therefore, research is needed on the characterization of ambient TEX concentration exposure in recreational runners, particularly in preferred running locations in Bandung City. The location and time of sampling was determined through a questionnaire that obtained 110 respondents. The top 3 preferred locations were Saraga Running Track, Gasibu Running Track, and Juanda Roadside. While the top 3 preferred running time were 16.00 – 19.00 PM, 07.00 – 10.00 AM, and 04.00 – 07.00 AM. The sampling was conducted using a GilAir Pump and Zefon Charcoal Tube, with each sampling location having 5 participants. The average duration and average pace for all participants are 44.725 minutes and 8.844 minutes/km respectively. Afterwards, the sample was then analyzed using GC-FID. The results showed that the total TEX concentration of Gasibu, Saraga, and Juanda are 337.148 µg/m3 , 144.772 µg/m3 , 407.600 µg/m3 respectively. Among the hydrocarbons studied, Toluene was the most dominant hydrocarbon among the sampling locations. Vehicle volumes and Meteorological factors are suspected to be the main factors affecting the concentration of these hydrocarbons. There is significant inverse correlation (???? < 0.1 ) with intermediate strength between running pace and ambient TEX concentration. Moreover, there is a significant difference between sampling locations and ambient TEX concentration which implies there is a correlation between concentration and sampling location.